Influence of nanoemulsfication, antioxidants and temperature on oxidative stability of red rapsberry seed oil for skin application - Gledović, Ana; Janošević Ležaić, Aleksandra; Savić, Snežana (Archives of Pharmacy, 2022)
In the past twenty years plant oils derived from food industry byproducts have been in focus due to the ecological and economic reasons. For example, raspberry seed oil – RSO (Rubus idaeus, Rosaceae), abundant with bioactive compounds such as polyunsaturated fatty acids, carotenoids, tocopherols and phenolic compounds, is recommended for antioxidant and UV-protective skincare. RSO application is limited by poor oxidative stability, thus this research aimed at its stabilization with nanoemulsion – NE carrier. Firstly, total carotenoid and phenolic content of RSO was determined, followed by determination of its oxidative status by tracking relevant parameters (peroxide value – PV, p-anisidine value – PA, and thiobarbituric reactive substances – TBARS) during one month of storage. NEs were prepared with the polyglycerol ester-based natural surfactants by employing phase inversion composition method, with or without RSO and antioxidants: synthetic (butylated hydroxytoluene – BHT or ethylenediaminetetraacetic acid, disodium salt – Na2EDTA), or sessile oak acorn extract (Quercus petraea, Fagaceae). NEs' physiochemical characterization included droplet size distribution analysis, electrical conductivity and pH value measurements, followed by measurement of primary and secondary oxidation products (lipid hydroperoxides – LH and TBARS, respectively). It was found that RSOs' oxidative stability was significantly improved when stored at refrigerator after opening or by adding BHT (PV˂10, PA˂6, % INH TBARS >80%). NEs were semitransparent (with very small droplets ˂70 nm) and stable at 25 and 40ºC, while drastic formation of oxidative products was avoided by employing BHT or Na2EDTA, or by using oak extract as natural stabilizer.